A LytM-Domain Factor, ActS, Functions in Two Distinctive Peptidoglycan Hydrolytic Pathways in E. coli - Chodisetti, Pavan Kumar; Bahadur, Raj; Amrutha, R. N.; Reddy, Manjula (Frontiers in Microbiology, 2022)
Bacterial cell wall contains peptidoglycan (PG) to protect the cells from turgor and environmental stress. PG consists of polymeric glycans cross-linked with each other by short peptide chains and forms an elastic mesh-like sacculus around the cytoplasmic membrane. Bacteria encode a plethora of PG hydrolytic enzymes of diverse specificity playing crucial roles in growth, division, or turnover of PG. In Escherichia coli, the cross-link-specific endopeptidases, MepS, -M, and -H, facilitate the enlargement of PG sacculus during cell elongation, whereas LytM-domain factors, EnvC and NlpD activate the division-specific amidases, AmiA, -B, and -C to facilitate the cell separation. In a screen to isolate additional factors involved in PG enlargement, we identified actS (encoding a LytM paralog, formerly ygeR) as its overexpression compensated the loss of elongation-specific endopeptidase, MepS. The overexpression of ActS resulted in the generation of partly denuded glycan strands in PG sacculi, indicating that ActS is either an amidase or an activator of amidase(s). The detailed genetic and biochemical analyses established that ActS is not a PG hydrolase, but an activator of the division-specific amidase, AmiC. However, interestingly, the suppression of the mepS growth defects by actS is not mediated through AmiC. The domain-deletion experiments confirmed the requirement of the N-terminal LysM domain of ActS for the activation of AmiC, but not for the alleviation of growth defects in mepS mutants, indicating that ActS performs two distinctive PG metabolic functions. Altogether our results suggest that in addition to activating the division-specific amidase, AmiC, ActS modulates yet another pathway that remains to be identified.